[Pyr1]-Apelin-13 delivery via nano-liposomal encapsulation attenuates pressure overload-induced cardiac dysfunction. (January 2015) - Serpooshan, Vahid; Sivanesan, Senthilkumar; Huang, Xiaoran; Mahmoudi, Morteza; Malkovskiy, Andrey V.; Zhao, Mingming; Inayathullah, Mohammed; Wagh, Dhananjay; Zhang, Xuexiang J.; Metzler, Scott; Bernstein, Daniel; Wu, Joseph C.; et al.
Abstract: Nanoparticle-mediated sustained delivery of therapeutics is one of the highly effective and increasingly utilized applications of nanomedicine. Here, we report the development and application of a drug delivery system consisting of polyethylene glycol (PEG)-conjugated liposomal nanoparticles as an efficient in vivo delivery approach for [Pyr1]-apelin-13 polypeptide. Apelin is an adipokine that regulates a variety of biological functions including cardiac hypertrophy and hypertrophy-induced heart failure. The clinical use of apelin has been greatly impaired by its remarkably short half-life in circulation. Here, we investigate whether [Pyr1]-apelin-13 encapsulation in liposome nanocarriers, conjugated with PEG polymer on their surface, can prolong apelin stability in the blood stream and potentiate apelin beneficial effects in cardiac function. Atomic force microscopy and dynamic light scattering were used to assess the structure and size distribution of drug-laden nanoparticles. [Pyr1]-apelin-13 encapsulation in PEGylated liposomal nanocarriers resulted in sustained and extended drug release both in vitro and in vivo . Moreover, intraperitoneal injection of [Pyr1]-apelin-13 nanocarriers in a mouse model of pressure-overload induced heart failure demonstrated a sustainable long-term effect of [Pyr1]-apelin-13 in preventing cardiac dysfunction. We concluded that this engineered nanocarrier system can serve as a delivery platform for treating heart injuries through sustained bioavailability of cardioprotective therapeutics.